2017
DOI: 10.1007/s00438-017-1407-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a major quantitative trait locus for bakanae disease resistance in rice by genome resequencing

Abstract: Bakanae disease (BD) has emerged as a serious threat in almost all rice cultivation regions worldwide. Nampyeong is a Korean japonica rice variety known to be resistant to BD. In this study, quantitative trait locus (QTL) mapping was performed with F2 and F3 plants derived from a cross between the Nampyeong variety and a susceptible Korean japonica line, DongjinAD. First, resequencing of Nampyeong and DongjinAD was performed, which identified 171,035 single nucleotide polymorphisms (SNPs) between the two paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Research groups in India (Fiyaz et al 2014 ), Korea (Kim et al 2014 ), and Taiwan (Chen et al 2019 ) used high-throughput inoculation methods to screen for resistant materials from 92, 500, and 231 diverse rice varieties, respectively. A total of 28 QTLs for bakanae resistance were mapped on rice chromosomes 1, 3, 4, 6, 8, 9, 10 and 11 (Volante et al 2017 ; Fiyaz et al 2016 ; Lee et al 2018 ; Cheon et al 2019 ; Ji et al 2018a ; Hur et al 2015 ; Lee et al 2019 ; Kang et al 2019 ; Yang et al 2006 ; Chen et al 2019 ). Chromosome 1, where 13 QTLs are located, appears to be particularly important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research groups in India (Fiyaz et al 2014 ), Korea (Kim et al 2014 ), and Taiwan (Chen et al 2019 ) used high-throughput inoculation methods to screen for resistant materials from 92, 500, and 231 diverse rice varieties, respectively. A total of 28 QTLs for bakanae resistance were mapped on rice chromosomes 1, 3, 4, 6, 8, 9, 10 and 11 (Volante et al 2017 ; Fiyaz et al 2016 ; Lee et al 2018 ; Cheon et al 2019 ; Ji et al 2018a ; Hur et al 2015 ; Lee et al 2019 ; Kang et al 2019 ; Yang et al 2006 ; Chen et al 2019 ). Chromosome 1, where 13 QTLs are located, appears to be particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome 1, where 13 QTLs are located, appears to be particularly important. Using four different bi-parental populations and rice diversity panel 1 (RDP1) (Cheon et al 2019 ; Ji et al 2018a ; Hur et al 2015 ; Lee et al 2019 ; Fiyaz et al 2016 ; Chen et al 2019 ), co-localized QTLs were fine-mapped to a region (21.36–24.37 Mb on chromosome 1) crucial for bakanae resistance. Although QTLs have been associated with mortality rate, disease incidence, disease severity, and F. fujikuroi colonization, no causal genes have been cloned and functionally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…These authors hypothesized that qBK1.1 and qBK1 (Hur et al 2015) might be the same QTL as they had overlapping positions. Ji et al (2017) found that QTL qFfR1 was located in a 230 kb region of rice chromosome 1 in Korean japonica variety Nampyeong, and suggested that the three QTLs qBK1, qBK1.1, and qFfR1 might indicate the same gene. Lee et al (2019) narrowed down the position of the qBK1 locus to a 35 kb region between InDel 18 and InDel 19-14, and revealed that location of qBK1 is close to those of qBK1.1, and qFfR1, does not overlapping each other.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we performed the fine mapping of the qBK1 locus related to bakanae disease resistance based on genotype and phenotype analyses of homozygous recombinants on the backcross progeny of Ilpum and Shingwang, using newly developed InDel and SNP markers. In addition to qBK1 , six QTLs have been identified on chromosome 1 including qBK1.2 / qBK1.3 / qBK1.1 from Pusa 1342 (Fiyaz et al 2016), qB1 from Chunjiang 06 (Yang et al 2006), qFfR1 from Nampyeong (Ji et al 2017), and qBK1 WD from Wonseadaesoo (Lee et al 2018). qBK1_628091 (0.6 Mbp to 1.0 Mbp on chromosome 1) and qBK4_31750955 (31.1 Mbp to 31.7 Mbp on chromosome 4) were revealed by GWAS approach using japonica rice germplasm collection (Volante et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These authors hypothesized that qBK1.1 and qBK1 (Hur et al 2015) might be the same QTL as they had overlapping positions. Ji et al (2017) found that QTL qFfR1 was located in a 230-kb region of rice chromosome 1 in the Korean japonica variety Nampyeong, and suggested that the three QTLs qBK1, qBK1.1 , and qFfR1 might indicate the same gene. In the present study, the qBK1 locus was narrowed to a 35-kb region between InDel 18 and InDel 19–14 in the 520-kb region on chromosome 1 identified in our previous study (Hur et al 2015).…”
Section: Discussionmentioning
confidence: 99%